PENYULUHAN KESEHATAN MENGENAI STIMULASI TUMBUH KEMBANG PADA BALITA DI TK PUI 2 SINDANG - Musthofa, Ali; Hidayatin, Titin; Hikmawati, Kitri; Hardivianty, Cyntihia; Juwita, Eka (Universitas Bhakti Kencana, 2024)
Growth and development is considered a single entity that reflects the various changes that occur during a person's life. All of these changes are dynamic processes that emphasize several interrelated dimensions. The development of toddlers is influenced by various factors that influence each other, including: the stimulation received by the child since infancy, the maturity of the child at the time of receiving stimulation, the innate nature of the child, the knowledge and attitude of parents towards the child and the interaction of parents with the child. Children under five really need developmental stimulation to achieve optimal growth and development. Therefore, growth and development stimulation activities in toddlers through health counseling and simulation of growth and development in toddlers. Parents (mothers) should carry out simulations continuously and continuously to achieve optimal toddler development and in accordance with the age of toddlers.